Women's sexuality and self-care in Primary Health Care: an integrative review (Research, Society and Development, 2021)
Sexuality is experienced and expressed in thoughts, fantasies, desires, beliefs, attitudes, values, behaviors, practices, roles, and relations. Women constitute the majority of the Brazilian population and are the main users of the Unified Health System. There is a need for information about this theme bearing in view in the cultural context when any problem related to sexuality afflicts women, they have no one to turn to. The present study aimed to evaluate women's sexuality and self-care in Primary Health Care from an integrative review. The search was conducted between August and September in the LILACS, MEDLINE, PUBMED and SciELO databases, resulting in 144 studies, of which 5 articles were used. Given the systematization of knowledge in the present approach, it was noticeable that there is a great deficit in the care provided to women's health, when observed the care focused on identifying diseases and solving treatment. There is no construction of integral care through the complaints that affect women's well-being. Furthermore, talking about sexuality with women is still a taboo, since users feel embarrassed to share their experiences and professionals are not prepared, representing an approach that is little discussed and not valued. At last, it is important to identify professional facilitators of this knowledge for this population, helping women to have freedom in sexuality and self-care with their bodies.